Legal Protection for Children as Heirs as Reviewed in Indo-nesian Family Law - Taufika Hidayati (Fox Justi : Jurnal Ilmu Hukum, 2025)
This study examines legal protection for children as heirs in the Indonesian family law system. Disparities in the treatment of children in various inheritance law systems applicable in Indonesia create legal uncertainty that has the potential to harm the interests of children. Using a normative juridical method with a legislative and case-based approach, the study found that the protection of children's inheritance rights is still fragmented in several legal systems that are sometimes contradictory. Harmonization of regulations is needed to place the principle of the best interests of the child as the primary consideration in the settlement of inheritance disputes, including strengthening the role of guardianship institutions in supervising the management of the inheritance of minors.